Pengaruh zakat terhadap pertumbuhan ekonomi, penggunaan dan penerimaan hasil cukai: Kajian perbandingan antara Indonesia dan Malaysia / Eko Suprayitno - Eko , Suprayitno (2017)
This study aims to look at the administration of zakat in Malaysia and Indonesia and the zakat effect on the economic growth, consumption and tax revenue. The development of zakat in Malaysian is administratively advanced as compared to Indonesia. This relates to the modelling, enforcement, regulation of zakat and the rule of zakat and tax policies. In Malaysia, the zakat administration is more systematic and efficient. Every state has their own management style, law enforcement, different policies, procedures and enforcements models. Similarly, in term of charity acts, every state has its own laws. But in zakat and tax policies, each country used centralization approach and little decentralization is utilized. In terms of policy zakat in Malaysia, zakat and taxation institutions practicing two systems of collection; collection after assesment and holding system, and zakat can be used as individual income tax rebates up to 100% but the maximum rebates for corporate zakat is about 2.5%. While in Indonesia, there are two types of zakat administration, namely the management of zakat by the government under Government Amil Zakat (BAZ) and by civil society or private institutions widely known as Amil Zakat Institution (LAZ). However, LAZ agencies are facing in-accountability issues due to failing to report amount of zakat collected to the central government. There were some institutions that are reluctant or unwilling to report directly to the government. In terms of law enforcement, in Indonesia, there has been no enforcement yet. The zakat payer received a small amount of rebate very much lower than zakat payer in Malaysia which a higher rebate and its rate 2.5% for individual income. For companies the government is not giving any tax rebate. This is a likely reason why zakat collection in Indonesia is still very small compared with the taxes revenue. This study is utilized panel data analysis to analyze the impact of zakat on selected macroeconomic variables, i.e. economic growth, consumption and tax revenue. The econometric approach used are panel unit root tests, ARDL, panel co-integration, panel data regression analysis with fixed effects models, and Granger Causality Test. In case of Malaysia, zakat has a positive effect on economic growth, consumption and on tax revenues. The hypothesis that zakat has a negative affect on tax revenues is rejected, because the results of the study in Malaysia showed that zakat has a positive effect on tax revenue. Granger causality test results also found that there is a long-term relationship or there were a co-integration between zakat and income; zakat and consumption; and zakat and tax revenue. The result of causality hypothesis suggests bi-directional causality hypothesis both in the long term and short term between zakat and income and with consumption and tax revenue. The significant link between zakat and those variables maybe related to an effective and efficient zakat management system. Therefore, in Malaysia this research believe that zakat can be used as one of instrument in fiscal policy. The purpose of zakat to provide a fair income distribution, to reduce poverty incidence, increase welfare of people and to install social justice. While in Indonesia, zakat has a positive effect on economic growth and consumption, while the effect on tax revenue is negative. The hypothesis which stated that the zakat will has a negative effect on tax revenue is accepted. This is probably caused by zakat payments as a reduction of taxable income was not effective in promoting the tax payers to pay zakat to the baitul maal. In case of Indonesia, Granger test results also found that there is a co-integration between zakat and income, as well as the zakat and economic growth, consumption and tax revenue. The relationship between zakat and economic growth, with consumption and with tax revenue suggests there is a bi-directional causality hypothesis in the long term. While in the short term there would be unidirectional causal hypothesis, zakat–economic growth hypothesis, zakat–consumption hypothesis and zakat–tax hypothesis.